PENGARUH PAJAK DAERAH DAN DANA ALOKASI UMUM TERHADAP ALOKASI BELANJA DAERAH DI KABUPATEN MAGETAN TAHUN 2009-2012 - antik sulistiyani (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2014)
This study aims to find out Local Taxes, General Allocation Funds, Regional Expenditure Allocations and the presence or absence of the influence of local taxes and general allocation funds on the allocation of local spending in Magetan District in 2009-2012. Data collection techniques use documentation. The data used in this study is the primary data obtained from the Realization of Local Tax Reports, General Allocation Funds and Report on Realization of Regional Expenditure In the Year 2009-2012 in Magetan District. This type of research is a quantitative descriptive research using multiple linear regression analysis technique. The results of data analysis show that local taxes have no effect because the local taxes in the achievement of targets do not meet the criteria ditetapakan. The General Allocation Fund has a positive and significant influence on the allocation of regional expenditure because DAU is a contribution from the central government with the aim of equity distribution of the financial capacity of the region